MEASUREMENT AND SUPPRESSION OF CUTTING TOOL VIBRATION USING PIEZOELECTRIC CERAMIC IN ANSYS - Jarral, A. T.; Pasha, R. A. (The Nucleus, 2013)
To measure vibration produced in lathe cutting tool various kinds of procedures are adopted. Small patch of piezoelectric ceramic material is successfully incorporated into turning cutting which is modeled in Pro Engineer and examined in finite element analysis to check vibrations in material cutting processes. Model and harmonic analysis are performed. The relative amplitudes of mode shapes and frequencies are identified by analyses which are causing chatter. The results are compared with the analysis which is performed without using piezoelectric material patch.